The Role of Implementing the Continuous Auditing Approach on Audit Quality within a Digital Transformation Environment: (A Theoretical Analytical Study) - Abdelmnam Mohamed Bilrras Ali, (Al-imad Journal of Humanities and Applied Sciences (AJHAS), 2026)
This study investigates the role of the continuous auditing approach in enhancing audit quality within the context of digital transformation. The research addresses the structural deficiencies of traditional auditing methods, particularly the reliance on sampling, which has become inadequate for managing large-scale data in modern business environments. By adopting a descriptive analytical methodology, the paper explores the concepts and objectives of continuous auditing and its capacity to mitigate discovery risks associated with electronic accounting systems. The findings reveal that integrating digital transformation technologies with continuous auditing allows for a comprehensive examination of entire data populations rather than limited samples, thereby providing real-time reports that enhance the reliability and transparency of financial statements. This transition from retrospective to proactive oversight enables early detection of material misstatements and fraud. However, the study identifies significant technical gaps among auditors and emphasizes the urgent need for professional retraining and the development of international auditing standards to accommodate emerging technologies like blockchain and cloud computing. Ultimately, the research concludes that continuous auditing is a strategic necessity for the sustainability of the profession, ensuring high-quality professional performance and reducing overall audit costs in a paperless environment. The study recommends that professional organizations update regulatory frameworks to bridge the gap between rapid data flow and traditional auditing speeds.